Potensi dan Manfaat Ekosistem Mangrove untuk Pengembangan Mata Pencaharian Alternatif Desa Karangsong: Mangrove Ecosystem Potency and Benefits for Alternative Livelihoods Development in Karangsong Village (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2023)
The sustainable development of alternative livelihoods is needed to preserve the mangrove ecosystem. Therefore, this study aims to determine the types of feasible alternative livelihoods to be developed. The method of data collection was carried out by literature studies, observations and surveys as well as participatory rural appraisal (PRA). The data were analyzed using the total economic valuation (TEV) method, welfare level analysis, business feasibility analysis, SWOT analysis, stakeholder relationship pattern analysis and rating scale analysis. The results recommend eight feasible MPAs to be developed in the coastal area of ​​Karangsong Village. They are mangrove syrup, mangrove dent, soy sauce, coffee, coastal wedang, lunkhead, chocolate, and fresh drinks. The eight MPAs shows that there are similarities in terms of providing raw materials and the availability of labor based on Rating Scale analysis. The total economic value (TEV) shows that direct benefits have the greatest economic value compared to indirect benefits. This can be interpreted that the economic benefits of the mangrove ecosystem will be greater if the ecosystem can be maintained properly, thus providing sustainable benefits. Based on the results of the study, it can be concluded that improving the welfare of the residents of Karangsong Village cannot rely on their current livelihood, but it is necessary to develop eight MPAs in a sustainable manner to improve the welfare of every coastal community household.